IMPLEMENTASI BAHAN AJAR PERSAMAAN GARIS LURUS BERINTEGRASI AL-QURAN PADA SISWA KELAS VIII SMP PUNGGUR - Winta Yuliani; Agung Hartoyo; Asep Nursangaji (Universitas Tanjungpura, 2021)
AbstractThis research aims to determine the implementation of the equation of the Qur'an integrated straight line. The method used in this study is an experimental method and this type of research is a pre-experimental design with a one-shot case study design. The population in this study was all grade VIII students of SMP, samples in this study selected one of the sample classes as an experimental class. Data collection techniques used are measurement techniques in the form of written tests, observation techniques and indirect communication techniques. Data collection tools used in this study are posttest, observation sheet of student learning results, and student questionnaire. Research data is analyzed descriptively. The results of this study showed that the ability of teachers in managing learning using The Qur'an's Integrated Straight Line Equation Teaching Materials are in a good category, the completedness of students' learning results using teaching materials integrating the Qur'an has not achieved a minimum of completedness. A total of 11 students out of 18 students in one class or 61% and classical completeness have not been met. So it can be concluded that learning using The Qur'an Integrated Teaching Materials is less effective to be applied in SMP.Keywords: Integrated Al-Qur'an, Implementation of Teaching Materials, Straight Line Equations.